An arteriovenous fistula following chalazion excision - Dias-Amborcar Yuri; Mokal Nitin; Abhyankar Suhas; Bhat Uday (Indian Journal of Plastic Surgery)
An arteriovenous fistula secondary to a chalazion is a rare occurrence. It may follow spontaneous necrosis or surgical trauma. Digital subtraction angiography and identification of the arterial feeders combined with direct puncture of the nidus and embolization is recommended, as surgical excision becomes much easier and results in a complete excision of the lesion. Conchal cartilage graft is a useful lining material for reconstruction of the tarsal plate due to its natural curvature. It restores lid integrity and ensures a stable and functional eyelid.